Ayurvedic Management of Schizoaffective disorder – A case report - P, Nima M; M, Jithesh; C, Santosh (Asian Journal of Pharmaceutical Research and Development, 2019)
Schizoaffective disorder is a chronic mental health condition characterized by symptoms of Schizophrenia such as hallucinations and delusions, and symptoms of a mood disorder such as mania or depression. As it shares the symptoms of more than a single mental health condition, many affected with schizoaffective disorder are often erroneously diagnosed. The disorder is seen in about 0.3% of the population as per reported studies and both men and women are equally prone to the disease. But men often develop the illness at an earlier age than women. The modern management includes use of both mood stabilizers and antipsychotics. Ayurveda psychiatry categorizes the disorder under the category of unmada which is considered as the vibhrama or distorted function of eight factors including manas and buddhi. A 48 year old male patient attended the Psychiatric OPD two months back. He had decreased sleep, lack of interest in attending the job, self-talking etc. He also complained about hearing of voices in ear. According to the informant, he had reduced social mingling and increased suicidal thoughts and had several attempts for committing suicide. He has been suffering from these complaints since past 18 years. The case was diagnosed as Vatakaphaja Unmada considering the dosha predominance and a protocol with special preference to sodhana procedures were performed after admission. The selected protocol was observed to be effective in managing the condition. The case report stresses the role of Ayurveda treatment modalities in managing similar psychiatric conditions. Keywords: